2023
DOI: 10.1002/elsc.202300219
|View full text |Cite
|
Sign up to set email alerts
|

Integration of a perfusion reactor and continuous precipitation in an entirely membrane‐based process for antibody capture

Gabriele Recanati,
Magdalena Pappenreiter,
Christoph Gstoettner
et al.

Abstract: Continuous precipitation coupled with continuous tangential flow filtration is a cost‐effective alternative for the capture of recombinant antibodies from crude cell culture supernatant. The removal of surge tanks between unit operations, by the adoption of tubular reactors, maintains a continuous harvest and mass flow of product with the advantage of a narrow residence time distribution (RTD). We developed a continuous process implementing two orthogonal precipitation methods, CaCl2 precipitation for removal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…For the experiment in which precipitate was directly fed to the system (steady-state emulation), the precipitated monoclonal antibody used was generated during an integrated perfusioncapture process. 33 Briefly, the CCCS was subjected to calcium chloride (CaCl 2 ) precipitation for the removal of impurities at a final concentration of 100 mmol L −1 CaCl 2 in 10 mmol L −1 MOPS, pH 7.0 by dilution of CCCS with a 1 M CaCl 2 stock solution in 0.1 mol L −1 MOPS, pH 7.0. The stream was clarified continuously by depth filtration and the monoclonal antibody was captured via PEG 6000 precipitation in a tubular reactor at a final concentration of 18% PEG 6000 in 30 mmol L −1 MOPS, pH 7.0 by dilution with a stock solution of 50% PEG 6000 in 100 mmol L −1 MOPS, pH 7.0.…”
Section: Precipitate Generation and Continuous Antibody Precipitationmentioning
confidence: 99%
See 2 more Smart Citations
“…For the experiment in which precipitate was directly fed to the system (steady-state emulation), the precipitated monoclonal antibody used was generated during an integrated perfusioncapture process. 33 Briefly, the CCCS was subjected to calcium chloride (CaCl 2 ) precipitation for the removal of impurities at a final concentration of 100 mmol L −1 CaCl 2 in 10 mmol L −1 MOPS, pH 7.0 by dilution of CCCS with a 1 M CaCl 2 stock solution in 0.1 mol L −1 MOPS, pH 7.0. The stream was clarified continuously by depth filtration and the monoclonal antibody was captured via PEG 6000 precipitation in a tubular reactor at a final concentration of 18% PEG 6000 in 30 mmol L −1 MOPS, pH 7.0 by dilution with a stock solution of 50% PEG 6000 in 100 mmol L −1 MOPS, pH 7.0.…”
Section: Precipitate Generation and Continuous Antibody Precipitationmentioning
confidence: 99%
“…The TFF stages remained identical, as the hollow fiber modules used still operate far below the critical flux in the range of 17-34 LMH. 33 For the laboratory-scale capture unit, we could describe the convoluted RTD generated via step input experiment with NaNO 3 with a TIS model, where N = 5, with a correlation coefficient of 0.96 (Fig. 4).…”
Section: Propagation Of Pulse and Step Inputsmentioning
confidence: 99%
See 1 more Smart Citation
“…Precipitation has been the dominant platform for plasma protein separations since the development of the Cohn fractionation process in the 1940s (Cohn et al, 1946; Foster et al, 1986). A number of recent investigations have demonstrated that precipitation can also be used for the purification of monoclonal antibodies (mAbs) (Dutra et al, 2020; Ferreira‐Faria et al, 2023; Li et al, 2019; Pons Royo et al, 2023; Recanati et al, 2023; Recanati et al, 2024), exploiting the relatively high titers of current Chinese hamster ovary (CHO) cell cultures (Liang et al, 2023; Shukla et al, 2017). The precipitated protein can be effectively dewatered and washed using tangential flow filtration (TFF), potentially providing a low‐cost platform for the continuous downstream processing of mAbs (Li et al, 2019; Minervini et al, 2023).…”
Section: Introductionmentioning
confidence: 99%